Stereodynamism in Pentacoordinate Al(Salen) Catalysts - Emanuel Studer; Walter R. Linke; Mia A. Müller; Constantin G. Daniliuc; Michael Ryan Hansen; Johannes Neugebauer; Ryan Gilmour (Journal of the American Chemical Society, 2026)
Abstract M(Salen) complexes are totemic in asymmetric catalysis on account of the generality and selectivity that they confer. Consequently, the development of unifying models to place the function of these disruptive actors on a structural foundation is essential to sustain innovation. Motivated by the transformative effect that the Jacobsen catalyst (M = Al) has had on contemporary synthesis, a thorough three-dimensional structural investigation of the solution phase behavior of Al(Salen) complexes is reported, and complemented by solid-state 27Al MAS NMR and computational investigations. This interdisciplinary analysis of the venerable Al(Salen)Cl complex reveals a rapid equilibrium of R,R-(M) and R,R-(P) species in solution enabled by intermolecular halide-catalyzed rearrangements. Contrary to established models, the backbone remains in the trans-diequatorial conformation: the antipodal (axial) configurations (M/P) are enforced by a change in coordination geometry between square based pyramidal (sbp) and distorted trigonal bipyramidal (dtbp). The occurrence of orthogonal helical diastereomers, with conserved point chirality [R,R-(M) and R,R-(P)] converges on a revised model to describe the behavior of pentacoordinate M(Salen) complexes based on the Addison geometry parameter τ. Stereodynamism resulting from dynamic metal coordination geometry is determined to be a key parameter that should be considered in future reaction design and induction models. It is envisaged that this intriguing behavior of pentacoordinate Al(Salen) complexes will find application beyond asymmetric catalysis.